(untitled) (American Journal of Human Psychology, 2023)
This research explored the personal and social challenges experienced by parents with both gays and lesbians’ children. Phenomenological research was used to investigate some of these challenges experienced by the parents. The participants were selected through snowballing techniques. Six (6) participants were selected to be the research participants. An in-depth interview guide was used to uncover the participants’ experiences. The interview questions were unstructured, validated by experts, and complemented by possible probing questions that will be used if deemed necessary. The researchers had one-on-one interviews with the participants. The researchers transcribed the entire recorded interview and thematically analyzed each conversation. It may be difficult to accept their child’s coming out as gay or lesbian at first, but as a parent, they have a broad mind, and as a mother, they choose to accept and understand their children’s feelings and personalities. Acceptance of gay and lesbian children raises concerns as well. In general, parents welcome their gay and lesbian children’s gender disclosure, in terms of fully accepting their children’s gender representations and responsiveness in which they express sympathy when their child is hurt or frustrated. However, it cannot deny that there is a deep conviction that being a man is meant for a woman, and being a woman is meant for a man, which results of not accepting their children as gender-diverse individuals.